2022
DOI: 10.12911/22998993/146269
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Trace Elements, Rare Earth Elements and Ecotoxicity in Sediments of the Kosva Bay, Perm Region (Russia)

Abstract: Over a long period of time, a huge amount of technogenic bottom sediments has been accumulating in the Kosva Bay with significant concentrations of amorphous iron and aluminium hydroxides, which, in turn, are active sorbents of pollutants. This study examines the distribution of trace elements and rare earth elements and their toxicity in the Kosva Bay of the Kama Reservoir (Perm Region, Russia). In the middle reach, the Kosva River crosses the Kizel coal basin, where acid mine water is discharged from closed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…где 𝑇 𝑟 𝑖 -коэф фициент токсичности i-го элемента, приведен для исследуемых элементов в табл. 1 по данным [27][28][29][30], а 𝐶 𝑓 𝑖 -коэффициент загрязнения этим элементом, также рассчитываемый по формуле:…”
Section: рис 2 современное расположение промканала г березники полож...unclassified
See 2 more Smart Citations
“…где 𝑇 𝑟 𝑖 -коэф фициент токсичности i-го элемента, приведен для исследуемых элементов в табл. 1 по данным [27][28][29][30], а 𝐶 𝑓 𝑖 -коэффициент загрязнения этим элементом, также рассчитываемый по формуле:…”
Section: рис 2 современное расположение промканала г березники полож...unclassified
“…𝑖 в депонирующих средах по данным [27][28][29][30] и средние концентрации микроэлементов в почвенном покрове фоновог о участка 𝐶 𝑛 𝑖 , мг /кг Вместе с RI производи тся расчет индекса геоаккумуляции (I g eo ), предложенного Г. М юллером [31]. I geo широко применяется для оценки уровня загрязн ения микроэлементами депонирующих сред: донных отложений природных водоёмов, почв, осадков сто чных вод [32,33].…”
Section: таблица 1 значения коэффициентов токсичности 𝑇 𝑟unclassified
See 1 more Smart Citation
“…Ecological risk studies have been based on the toxicity coefficients of REYs, for which it was reported that they were similar to those of HMs [ 33 ]. It was reported that the ecological risks due to the REY presence in soil [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ], sediment [ 41 , 42 , 43 , 44 ], and street dust were relatively low. Moreover, the estimated non-cancer and cancer human health risks from soil [ 45 , 46 , 47 ], sediments [ 48 ], air [ 49 ], and the consumption of vegetables fall below the acceptable safety limits [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%